English annoted translation of tourist advertising material as a contribution to the town hall of Santa Rosa-Provincia de El Oro. - Vilela Pacheco, Denisse Andrea (2015)
The town of Santa Rosa is a place where people can find a wide variety of tourist attractions among them there are rivers, beaches, parks, extraordinary seafood, and its internationally recognized Annual Shrimp Festival. This city also has an airport equipped with modern facilities, as well as cozy restaurants located along the harbor. These places seem to be empty most of the times, which is not only a waste of resources, but also a pity. Given the aforementioned fact, and after deep research about the information of the city available for national and international tourists, it was found that almost all the existing material was only Spanish, except for one brochure prepared by the Ecuadorian Ministry of Tourism which contains bilingual information. This brochure, which seems to have undergone machine translation, is the only source of information for potential foreign visitors who do not speak Spanish. Once this problem was spotted, the major of the town was asked about this particular issue and he said to be informed and worried about not being able to overcome the language barrier and attract not only foreign visitors, but also foreign investment. In view of this fact, he agreed to delegate the work and accept the professional translation of the material offered at no cost, guaranteeing the use of adequate techniques and applying all the semantic, cultural, linguistic and syntactic structures needed for this sort of material.